UPAYA MENINGKATKAN KEDISIPLINAN GURU MELALUI KETELADANAN KEPALA SEKOLAH DI MTsN 2 SIMEULUE - SEPTIMI HARTATI NATALIA (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2023)
This research serves to analyze increasing teacher discipline through the example of the school principal at MTsN 2 Simeulue. This study uses a qualitative method. The results of this research conclude that the role of the principal through his example is the most important thing in improving teacher discipline, because the principal is someone who is emulated, imitated and encouraged by teachers as a leader. as a leader in a school, the head has several functions including: the principal as an educator or educator, the principal as a manager who is essentially a planner, organizer, and supervisor, the principal as an administrator who is responsible for the smooth running, implementation and teaching of the school, the principal as a supervisor who can develop and assist teachers in improving their competence, the principal as a leader who sets an example, the principal as an innovator who must have a strategy to establish harmony in the school environment and be able to develop innovative learning models, and the final function of the principal is as a motivator which has strategies to provide motivation to teachers in carrying out their duties and functions. In this research, there are benefits felt at school, namely that teachers at MTsN 2 Simeulue can change their undisciplined habits to become people who are disciplined and respect their time on duty. ABSTRAKPenelitian ini berfungsi untuk menganalisa tentang peningkatan kediplinan guru melalui keteladanan kepala sekolah pada MTsN 2 Simeulue. Penelitian ini menggunakan métode kualitatif. Hasil penelitian ini menyimpulkan bahwa peranan kepala sekolah melalui keteladannya adalah suatu hal yang paling penting dalam meingkatkan kedisiplinan guru, karena kepala sekolah merupakan orang yang dicontoh, ditiru dan diguguh oleh Guru sebagai pimpinan. sebagai pemimpin dalam suatu sekolah, kepala memiliki beberapa funsi diantaranya: Kepala sekolah sebagai edukator atau pendidik, kepala sekolah sebagai manager yang pada hakekatnya seorang perencana organisator, dan pendali, kepala sekolah sebagai administrator yang bertanggung jawab atas kelancaran, pelaksanaan dan pengajaran disekolah, kepala sekolah sebagai supervisor dimana dapat membina dan membantu guru dalam meningkatkankan kompetensinya, kepala sekolah sebagai leader yang memberi keteladan, kepala sekolah sebagai inovator yang harus memiliki sstrategis untuk menjalin keharmonisan dalam lingkungan sekolah dan mampu mengembangkan model pembelajaran yang inovasi, dan fungsi terakhir kepala sekolah adalah sebagai motivator yang memiliki strategi untuk memberikan motivasi pada guru dalam melakukan tugas dan fungsinya. Dalam penelitian ini terdapat manfaat dirasakan disekolah yaitu guru-guru yang ada pada MTsN 2 Simeulue dapat merubah kebiasaannya yang tidak disiplin menjadi orang yang disiplin dan menghargai waktu pada tugasnya.